LOW ENGLISH PROFICIENCY STUDENTS’ ORAL INTERACTION WITH NATIVE SPEAKER THROUGH SKYPE - Imelda Wahyuni Husein; Pupung Purnawarman (Edusentris, 2019)
There are many students in Indonesia who are afraid of speaking in English. The lack of vocabulary, fluency, accuracy, and also exposure makes it difficult for students to be confident speaking English. This study aimed to investigate how low English proficiency students interact with a native speaker of English and what they feel following the conversation. This study used qualitative research involving four 10th grade students in one of vocational high schools in Bandung, Indonesia. The sample was taken purposively in order to get the uniqueness. Observations were conducted in this study to observe four low English proficiency students’ interaction with native speaker of English during 10 meetings. An interview was also conducted to find out what students feel when they have a conversation and whether they feel an improvement in their speaking skill. The data were collected based on observation and interview results. According to the observation findings, low English proficiency students experience an improvement in their speaking skill after interacting with a native speaker even if they faced difficulties. The interview results show that they are more confident in speaking English after having a conversation with a native speaker. Therefore, it is suggested that if it is necessary, the teachers make a collaboration or work together with native speakers in order to improve students’ speaking skill.